Vaccination in Individuals with Multiple Sclerosis – Part II - Aslı Tuncer; Bilge Piri Çınar; Nuray Bilge; Sena Destan Bünül; Rabia Gökçen Gözübatık Çelik; Eda Derle Çiftçi; Gencer Genç; Bedriye Karaman; Ahmet Kasım Kılıç; Alp Sarıteke; Meral Seferoğlu; Ali Özhan Sıvacı; et al. (Türk Nöroloji Dergisi, 2023)
Multiple sclerosis (MS) is an autoimmune and demyelinating disease of the central nervous system. It is a chronic disease, and in the evaluation of all other health and vital processes, decisions about vaccination should be made considering the disease process and the medications used by the patient. Since vaccination can be performed at any stage of life, immune system activity should be reviewed in patients with MS except where it is characteristic of the vaccine. In this review, the applications of different vaccines in patients with MS are discussed in two separate sections (part 1 was published in the previous issue).